Geochemical and isotopic structure of the early Palaeozoic active margin of Gondwana in northern Victoria Land, Antarctica - ROCCHI, SERGIO; ARMIENTI, PIETRO; INNOCENTI, FABRIZIO; Tonarini S.; Manetti P. (Tectonophysics, 1998)
The regional distribution of geochemical and isotopic compositions of granitoid rocks from a Gondwana continental margin is studied to highlight its structure and geodynamic evolution. The intrusive rocks emplaced during the early Palaeozoic Ross Orogeny in northern Victoria Land (Antarctica) constitute a high-K calc-alkaline association. The geographic patterns of isotope and geochemical data on granitoid rocks allow the distinction of two portions of the continental margin, separated by a sharp discontinuity. The portion towards the palaeo-Pacific Ocean (Oceanward Side) displays strongly regular inland increase of Sr-and decrease of Nd-isotope ratios, coupled with analogous variations in major and trace elements; on this basis we infer a NW-SE-trending margin affected by SW-directed subduction. The portion towards the East Antarctic Craton (Continentward Side) shows a similar regular variation only for Nd isotope compositions, consistent with a hypothesis of a N-S-striking margin with west-ward subduction. In the Oceanward suggest that the granites were generated by extensive interaction of Side, isotope and trace-element characteristics suggest that the granites were generated by extensive interaction of mantle-derived magmas with high-level crustal melts. The origin of Continentward Side intrusives is compatible with a process of interaction between mantle-derived melts and a mafic granulite lower crust. The granitoids of the two crustal sectors share the same Proterozoic Sm-Nd model ages, suggesting that they both belong to the same crustal province. We interpret this arrangement of crustal segments as due to the shift and rotation of a forearc sliver of the Gondwana margin, This movement was likely enhanced by oblique subduction under an irregular margin weakened by the presence of a magmatic are. (C) 1998 Elsevier Science B.V. All rights reserved.